2014
DOI: 10.1134/s0036024414110168
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-chemical processes under the conditions of laser ablation of metals in aqueous media (problems of “cold fusion”)

Abstract: A brief review of results on initiation of nuclear transformations under conditions of the laser abla tion of metals in aqueous media upon exposure to picosecond laser impulses with peak intensity J E ∼ 10 10 -10 13 W/cm 2 , which is orders of magnitude less than required for the direct initiation of nuclear processes, J E ∼ 10 18 -10 19 W/cm 2 , is presented. It is shown that the decay rate of radioactive nuclei (using the example of uranium 238) increases significantly (by orders of magnitude), nucleus trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…We also give examples [17,20] 27 Co agree with this conclusion: the half-life of β --active cesium-137 and barium-140 nuclei, equal to 30.1 years and 12.8 days, respectively, decreased to about 380 days and 2.7 days, while the halflife of cobalt-60, equal to 1925 days, remained practically unchanged. The Feynman diagrams corresponding to the β --decay processes, as well as the positron β + -decays of nuclei initiated by the е --catalysis mechanism, are shown in Fig.…”
Section: Electronic Factor In Initiating Nuclear Processessupporting
confidence: 79%
See 4 more Smart Citations
“…We also give examples [17,20] 27 Co agree with this conclusion: the half-life of β --active cesium-137 and barium-140 nuclei, equal to 30.1 years and 12.8 days, respectively, decreased to about 380 days and 2.7 days, while the halflife of cobalt-60, equal to 1925 days, remained practically unchanged. The Feynman diagrams corresponding to the β --decay processes, as well as the positron β + -decays of nuclei initiated by the е --catalysis mechanism, are shown in Fig.…”
Section: Electronic Factor In Initiating Nuclear Processessupporting
confidence: 79%
“…In this paper, it is shown that the problems of establishing the possible mechanisms of LENR processes discussed above can be understood on the basis of the concepts of the interrelation between the electronic and nuclear subsystems of an atom [16][17][18][19][20], which determines the possibility of initiating the entire variety of nuclear transformations, including those studied in mentioned works [7][8][9][10][11][12][13], as well as realized in the Andrea Rossi E-CAT reactor [21,22].…”
Section: Al(mentioning
confidence: 99%
See 3 more Smart Citations